The Role of Physical Therapy Exercises in Enhancing Sexuality in Patients with Incontinence: A Systematic Review - Chang, Yu-Shuan (South East Asia Nursing Research, 2023)
Incontinence, particularly urinary incontinence, is a prevalent condition that significantly affects patients' quality of life, including their sexual health. Physical therapy exercises, especially pelvic floor muscle training (PFMT), have been recognized as effective interventions for managing incontinence and enhancing sexual function. This systematic review aims to evaluate the role of physical therapy exercises in improving sexual health among patients with incontinence. A total of 15 studies were included, highlighting the positive impact of these exercises on sexual satisfaction, frequency of intercourse, and overall sexual well-being. The findings suggest that incorporating physical therapy exercises, particularly PFMT, into the management of incontinence can lead to significant improvements in sexual health. However, further research is necessary to standardize exercise protocols and explore long-term outcomes.